Study of adsorption kinetics by volumetric method - Muhammad Sufiyan Suhaini. (2012)
There is a huge demand for cleaner energy to reduce the anthropogenic emissions of carbon dioxide into the atmosphere. With that in mind, a theoretical framework is proposed to study physical gas adsorption of carbon dioxide on activated carbon, “Maxsorb-III”, at isothermal conditions to establish its experimental fit with different isotherm models. The overarching study of gas adsorption in this report are twofold; firstly, adsorption at equilibrium conditions and secondly, adsorption kinetics.